Numerical Solution for Linear Delay Fourth Order Multi-Value Problems (Journal of the College of Basic Education, 2023)
This paper attempts to study the linear delay fourth order multi-value problems, and modify one of the powerful numerical methods namely the variational technique to solve this kind of problems.